Droplet Fusion in Oil-in-Water Pickering Emulsions - Whitby, Catherine P.; Bahuon, Floriane (Frontiers in Chemistry, 2018)
We have formed compound droplets made of two or more drops of immiscible oils by temporarily destabilizing Pickering oil-in-water emulsions. The emulsions used are synergistically stabilized by mixtures of cationic surfactant and negatively-charged particles. They are highly sensitive to the concentration of surfactant present in the emulsions. We took advantage of transient droplet coalescence events that are triggered by reducing the surfactant concentration to fuse together drops of immiscible oils. This study provides guidelines for designing compound droplets by transient (or limited) coalescence in Pickering emulsions. We show that the possible geometries of particle-stabilized compound drops are determined by the interfacial tensions and relative volumes of the drops fused together. The implications of our results for designing strategies to fabricate multiphase drops are discussed.